Space, innovation and the locus of knowledge: an ontological response to Rutten. (1st March 2014) - Bahlmann, Marc D.
Abstract : Marc Bahlmann is assistant professor at VU University Amsterdam. He received his Ph.D. from the Faculty of Social Sciences (VU University) for a study on knowledge dynamics among IT entrepreneurs located in the Amsterdam IT and new media cluster. His current research interests include alliance portfolios, organizational and regional innovation.